(untitled) (University of Khartoum Engineering Journal, 2022)
This paper presents an empirical correlation deduced to predict Nitrogen Oxides (NOX) emissions form a turbocharged diesel engine (TC engine) when using inlet manifold water injection as a suppressant NOX emissions. NOX emissions are determined as a function of different engine operating parameters such as engine speed, brake power, and the rate of injected water that are measured during the experiments. The experimental results showed that NOX emissions are significantly affected by changes in engine speed, brake power and rate of injected water. The NOX model presented in this paper can be used as a research tool, particularly in studying the way in which diesel engine design influences exhaust emissions.